Prevalence of household food insecurity and its association with food waste - Rian Diana; Drajat Martianto; Yayuk F. Baliwati; Dadang Sukandar; Agung Hendriadi (SpringerOpen, 2024)
Abstract Background Household food waste significantly contributes to overall food waste. While the relationship between food security and food waste has been extensively studied at the macro level, there is a need for research focusing on the quantitative association between food security and food waste at the household level in developing countries, particularly in Southeast Asia. This study aims to estimate the prevalence of household food insecurity and household food waste and to examine the association between household food security and food waste using direct measurements. Subjects and methods A total of 215 households in Bogor Regency, Indonesia, participated in this cross-sectional study. Food waste was measured using waste composition analysis and a 7-day diary. The Food Insecurity Experience Scale (FIES) questionnaire was used to assess household food security, while household income and the proportion of food expenditure were considered confounding factors. The association between food security and food waste was examined using Kendall tau-b and ordinal logistic regression. Results The prevalence of household food insecurity was 18.6%, and the average household food waste was 77 kg/cap/year. Cereals, tubers, and their derivatives (especially rice) and vegetables were major contributors to edible waste, while fruits dominated inedible waste. A negative association was observed between food waste and household food security (edible FW: p = 0.044, r = -0.110; total FW: p = 0.038, r = -0.114), suggesting that household food waste decreases as the severity of food insecurity increases. However, after adjusting for household income, the proportion of food expenditure, and the education levels of spouses, this association became statistically insignificant (p > 0.05). Conclusion There was no significant association between household food security status and food waste. Household income plays a significant role in determining the quantity of household food waste, as higher income is associated with increased food waste. Strategies to prevent and reduce food waste should focus on major contributors such as rice and vegetables, especially among families with higher food accessibility.